2010
DOI: 10.1309/ajcphmyt93huizkw
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Thymidine Kinase 1 Level Predicts Poorer Survival in Patients With Chronic Lymphocytic Leukemia

Abstract: Serum thymidine kinase 1 (TK1) levels have been reported to have prognostic significance in patients with chronic lymphocytic leukemia (CLL). Until recently, serum TK1 levels were assessed using inconvenient radioenzyme assays. In this study, we used a novel chemiluminescence assay to assess serum TK1 levels in patients with CLL at the time of first examination. We show that high serum TK1 levels predict poorer overall survival and correlate with unmutated immunoglobulin variable region genes, CD38 and ZAP-70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
3
25
0
2
Order By: Relevance
“…Among patients with newly diagnosed CLL/SLL, the annual incidence rate of DLBCL is 0.5%; whereas among patients who have received treatment for CLL/SLL the annual incidence rate of DLBCL is 1% [15]. Up to 10.7% of all CLL/SLL patients progress to DLBCL (RS-DLBCL) [11,12,14,15,[20][21][22][23] (Supporting Information Table I). The incidence rate for DLBCL reported in the literature is highly variable, likely attributable to many factors including the heterogeneity of the patient population studied, duration of clinical follow-up, and diagnostic criteria used to define development of DLBCL (clinical/imaging vs. biopsy-proven).…”
Section: Histologic Variants Of Richter Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with newly diagnosed CLL/SLL, the annual incidence rate of DLBCL is 0.5%; whereas among patients who have received treatment for CLL/SLL the annual incidence rate of DLBCL is 1% [15]. Up to 10.7% of all CLL/SLL patients progress to DLBCL (RS-DLBCL) [11,12,14,15,[20][21][22][23] (Supporting Information Table I). The incidence rate for DLBCL reported in the literature is highly variable, likely attributable to many factors including the heterogeneity of the patient population studied, duration of clinical follow-up, and diagnostic criteria used to define development of DLBCL (clinical/imaging vs. biopsy-proven).…”
Section: Histologic Variants Of Richter Transformationmentioning
confidence: 99%
“…Konoplev et al [23] showed that CLL/SLL patients with increased serum thymidine kinase 1 (TK1), a key cellular enzyme involved in DNA synthesis, are at higher risk for developing RS. Increased serum TK1 level is associated significantly with male sex, elevated serum b2M level, unmutated IGVH, ZAP-70 expression, and lack of del(13q14.3).…”
Section: Histologic Variants Of Richter Transformationmentioning
confidence: 99%
“…A significant correlation showing that high serum TK1 levels predict poorer patient survival was detected by a novel chemiluminescence immunoassay (CLIA) technique (20). This novel method does not require radioactivity and is convenient and rapid.…”
Section: Thymidine Kinase 1 As a Diagnostic Tumor Marker Is Of Moderamentioning
confidence: 99%
“…The majority of the studies on TK1 included in the present meta-analysis assessed the diagnostic accuracy in different methods and different types of tumors (1,9,12,16). Initial studies investigating the prognostic significance of serum TK1 levels in patients with chronic lymphocytic leukemia (CLL) were conducted using a radioenzymatic assay (REA) (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Both serum Beta 2 microglobulin (2M) 6 and serum thymidine kinase 1 (sTK) [7][8][9][10][11] are independent markers of progression free and overall survival in trials of chemotherapy and chemo-immunotherapy. Soluble CD23 (sCD23) is associated with shorter PFS and OS in early stage patients [12][13][14][15][16] and the doubling time of sCD23 appears more powerful than sCD23 12 .…”
Section: Introductionmentioning
confidence: 99%